Dinamika Kelompok Tani Hutan Desa (KTHD) Bontomarannu Di Desa Labbo, Kecamatan Tompobulu, Kabupaten Bantaeng - Nuranita Nuranita; Muhammad Dassir; Makkarennu Makkarennu (Fakultas Kehutanan, Universitas Hasanuddin, 2020)
Group Dynamics are powers, movements, or changes which occur within a group and influence its members in achieving their purposes. This research aims to determine the group dynamics of Village Forest Farmers Community at Labbo Village, Tompobulu Sub-District, Bantaeng District. The research was conducted in Labbo Village, Tompobulu District, Bantaeng. The data collection process was conducted by using qualitative approach that describes circumstances or events regarding humans’ states or behaviors in particular places in a deep and detail manner. Data collection process was done by interviewing 15 samples that were chosen by purposive sampling. The results of these interviews would be then analyzed by using descriptive analysis. Based on the 8 group dynamics elements, the research found that the group dynamics of Bontomarannu Village Forest Farmers Community, could be categorized as dynamic